Antara Tradisi, Sosial dan Budaya serta Peran Hukum Sebagai Upaya Memutus Penularan Covid -19 - Endang Suprapti; Eni Jaya; Arihta Esther Tarigan; Jum Anggriani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Corona Pandemic (Corona Virus Desease) or often referred to as Covid-19 is a world concern today, outbreaks that have existed include Sars and Avian Flu. Unlike its predecessor, the spread of which was not so massive as Covid-19. Indonesia is one of the countries affected by the outbreak. What are the regulatory steps for the government to break the chain of transmission of the Covid-19 outbreak. Research Methods: This type of descriptive qualitative research is normative in nature, the legal materials used are: primary legal materials and secondary legal materials with a statute approach and a conceptual approach. Primary legal materials collected include legal materials obtained from informants and legal materials on a variety of policies, regulations for handling infectious diseases or epidemics. Secondary legal materials are in the form of regional policies on the implementation of PSBB and other documents. The conclusion of the phenomenon of the emergence of an epidemic based on the various socio-cultural characteristics of the nation as implied in the motto of Unity in Diversity cannot be denied, namely wealth as well as obstacles to law in breaking the chain of Covid-19 transmission, based on existing regulations, can be used as a legal umbrella against prevention of the spread of Covid-19. Suggestion: Discipline is the key to successfully controlling the spread of Covid-19Keywords; Socio-Culture, Transmission, Covid-19AbstrakPandemi Corona (Corona Virus Desease) atau sering disebut dengan Covid-19 menjadi perhatian dunia saat ini, wabah yang pernah ada antara lain Sars dan Flu Burung. Berbeda dengan pendahulunya yang penyebarannya tidak begitu masif seperti Covid-19. Indonesia merupakan salah satu negara yang terkena dampak wabah tersebut. Apa saja langkah regulasi yang dilakukan pemerintah untuk memutus mata rantai penularan wabah Covid-19. Metode Penelitian: Jenis penelitian deskriptif kualitatif ini bersifat normatif, bahan hukum yang digunakan adalah: bahan hukum primer dan bahan hukum sekunder dengan pendekatan undang-undang dan pendekatan konseptual. Bahan hukum primer yang dikumpulkan meliputi bahan hukum yang diperoleh dari informan dan bahan hukum tentang berbagai kebijakan, peraturan penanganan penyakit menular atau wabah. Bahan hukum sekunder berupa kebijakan daerah tentang pelaksanaan PSBB dan dokumen lainnya.. Kesimpulan dari fenomena munculnya wabah penyakit berdasarkan berbagai karakteristik sosial budaya bangsa sebagaimana tersirat dalam semboyan Bhinneka Tunggal Ika tidak dapat dipungkiri yaitu kekayaan sekaligus hambatan hukum dalam memutus mata rantai penyebaran Covid- Transmisi 19, berdasarkan regulasi yang ada, dapat dijadikan payung hukum pencegahan penyebaran Covid-19. Saran: Disiplin adalah kunci sukses mengendalikan penyebaran Covid-19Kata kunci: Sosial budaya, Penularan, Covid-19